An Analysis on Policy Direction of Community Based Management of Mangorove Ecosystem in Sungai Pisang Bungus Teluk Kabung District in Padang City - Refinda, Guni (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research was motivated by lack of understanding and public awareness in the management of mangrove ecosystem. This was due to the community lack of knowledge on how to take advantage of mangroves in coastal and tidal areas. The purpose of this study was to know the community Participation, Strategy of Mangrove Management and to formulate appropriate policies of CBM based mangrove management. This research was a mixed method research or a combination of quantitative and qualitative research. Research findings indicated that the participation of Sungai Pisang Community in managing the mangrove ecosystem had not gone well and the students were nor aware of mangrove management. By using the aspect of Mangrove management such as the aspect of strength, threat. Weaknesses, and opportunities, 9 strategies were formulated, namely: (1) Local rules about Mangrove ecosystem management need to be written, (2) CMB-based Mangrove nurseries program, (3) Performing preventive action by approaching and developing local people awareness of appropriate technology for Mangrove area, which is also called Silvofishery. (4) Giving strict punishment to the people who were destroying mangroves for private purposes, (5) Optimization and rehabilitation of vacant land into a mangrove forest, (6) Returning the local wisdom in managing coastal areas, (7) Following counseling and training on mangrove management, (8) Improving supervision and monitoring, (9) Dividing the duties, functions and responsibilities of stakeholders according to their expertise. Based on those strategies, policy priorities were formulated. They are: are(1) Following the counseling and training on mangrove management, (2) Optimizing and rehabilitatingthe vacant land into a mangrove forest, (3) Increasing supervision and monitoring, (4) returning local wisdom in coastal area.